Effects of steaming on health-valuable nutrients from fortified farmed fish: Gilthead seabream (Sparus aurata) and common carp (Cyprinus carpio) as case studies. (June 2021) - Barbosa, Vera; Maulvault, Ana Luísa; Anacleto, Patrícia; Santos, Marta; Mai, Mónica; Oliveira, Helena; Delgado, Inês; Coelho, Inês; Barata, Marisa; Araújo‐Luna, Ravi; Ribeiro, Laura; Eljasik, Piotr; et al.
Abstract: Fish fortification with iodine-rich macroalgae ( Laminaria digitata ) and Selenium-rich yeast is expected to promote nutritional added value of this crucial food item, contributing to a healthy and balanced diet for consumers. However, it is not known if steaming can affect these nutrient levels in fortified fish. The present study evaluates the effect of steaming on nutrients contents in fortified farmed gilthead seabream ( Sparus aurata ) and common carp ( Cyprinus carpio ). Fortified seabream presented enhanced I, Se and Fe contents, whereas fortified carp presented enhanced I, Se and Zn contents. Steaming resulted in increased I and Se contents in fortified seabream, and increased Fe and Zn levels in fortified carp, with higher elements true retention values (TRVs >90%). The consumption of 150 g of steamed fortified seabream contributes to a significant daily intake (DI) of I (up to 12%) and Se (up to >100%). On the other hand, steamed fortified carp contributes to 19–23% of I DI and 30%–71% of Se DI. These results demonstrate that steaming is a healthy cooking method, maintaining the enhanced nutritional quality of fortified fish. Moreover, the present fortification strategy is a promising solution to develop high-quality farmed fish products to overcome nutritional deficiencies.